Imp and Syp mediated temporal patterning of neural stem cells in the developing Drosophila CNS. - Islam, I.M.; Erclik, T. (Genetics, 2022)
The assembly of complex neural circuits requires that stem cells generate diverse types of neurons in the correct temporal order. Pioneering work in the Drosophila embryonic ventral nerve cord has shown that neural stem cells are temporally patterned by the sequential expression of rapidly changing transcription factors to generate diversity in their progeny. In recent years, a second temporal patterning mechanism, driven by the opposing gradients of the Imp and Syp RNA-binding proteins, has emerged as a powerful way to generate neural diversity. This long-range temporal patterning mechanism is utilized in the extended neural stem cell lineages of the postembryonic fly brain. Here, we review the role played by Imp and Syp gradients in several neural stem cell lineages, focusing on how they specify sequential neural fates through the post-transcriptional regulation of target genes, including the Chinmo and Mamo transcription factors. We further discuss how upstream inputs, including hormonal signals, modify the output of these gradients to couple neurogenesis with the development of the organism. Finally, we review the roles that the Imp and Syp gradients play beyond the generation of diversity, including the regulation of stem cell proliferation, the timing of neural stem cell lineage termination, and the coupling of neuronal birth order to circuit assembly.